The Double Man: W. H. Auden’s Transatlantic Transformation - Partyka, Jacek (Text Matters: A Journal of Literature, Theory and Culture, 2015)
The paper attempts to consider the problem of W. H. Auden’s political engagement in the 1930s in the context of his (in)famous decision to leave England and settle down in the USA. The transatlantic journey of the eponymous member of so-called “Auden generation” prompted certain critics (notably Randall Jarrell) to set up a distinct caesura between the “English” and the “American” Auden, giving primacy to the accomplishments of the former and downplaying the works of the latter. As it is argued, America was not the place of the poet’s radical volte-face, but only a certain important, logical stage (and not a final one) in his personal and poetic evolution. His entanglements with politics were often mythologized, and occasional public and semi-political verse he “committed” often tended to subvert any attempts to pigeonhole the author in terms of his ideological stance.